Modeling a Metamorphic Aquifer through a Hydro-Geophysical Approach: The Gap between Field Data and System Complexity - Francesco Chidichimo; Michele De Biase; Francesco Muto; Salvatore Straface (Hydrology, 2023)
The productivity of metamorphic aquifers is generally lower than that of the more common alluvial and carbonates ones. However, in some Mediterranean areas, such as the Calabria region (Italy), water scarcity combined with the presence of extensive metamorphic water bodies requires the development of further studies to characterize the hydrodynamic properties of these groundwater systems in order to achieve their sustainable exploitation. The interest in this goal becomes even greater if climate change effects are considered. The purpose of this study was to provide the geological-structural and hydrogeological numerical modeling of a metamorphic aquifer, using direct and indirect data measurement, in a large area of the Sila Piccola in Calabria. The hydrodynamic characterization of the crystalline-metamorphic aquifer, constituted by granite and metamorphic rocks, is extremely complex. The MODFLOW-2005 groundwater model was used to simulate flow phenomena in the aquifer, obtaining hydraulic conductivity values of 2.7 × 10−6 m/s, which turned out to be two orders of magnitude higher than those obtained from the interpretation of the slug-tests performed in the study area. The mathematical model was also able to estimate the presence of a lateral recharge from a neighboring deep aquifer providing a significant water supply to the system under investigation.